The Hardy boys forever lost - Dixon, Franklin W. (Aladdin New York, 2011)
After managing to escape from an underground bunker where he was imprisoned for two days, Frank, along with his brother Joe, continues to investigate the disappearance of eight children from Misty Falls State Park in Idaho